2006
DOI: 10.1056/nejmoa054692
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Inhaled Corticosteroids in Infants with Episodic Wheezing

Abstract: Intermittent inhaled corticosteroid therapy had no effect on the progression from episodic to persistent wheezing and no short-term benefit during episodes of wheezing in the first three years of life. (ClinicalTrials.gov number, NCT00234390.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
365
2
19

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 511 publications
(389 citation statements)
references
References 39 publications
3
365
2
19
Order By: Relevance
“…Treatment of episodic (viral) wheeze in preschool children to reduce risk of persistent wheeze during later childhood Three randomised controlled trials (two on daily ICSs and one on intermittent use when the child was wheezy) have shown that use of ICSs in preschool children with episodic (viral) wheeze does not reduce the risk of persistent wheeze at the age of 6 yrs, and that symptoms return when steroid therapy is discontinued [41,119,120].…”
Section: Nasal Corticosteroids To Reduce Episodic (Viral) Wheezementioning
confidence: 99%
“…Treatment of episodic (viral) wheeze in preschool children to reduce risk of persistent wheeze during later childhood Three randomised controlled trials (two on daily ICSs and one on intermittent use when the child was wheezy) have shown that use of ICSs in preschool children with episodic (viral) wheeze does not reduce the risk of persistent wheeze at the age of 6 yrs, and that symptoms return when steroid therapy is discontinued [41,119,120].…”
Section: Nasal Corticosteroids To Reduce Episodic (Viral) Wheezementioning
confidence: 99%
“…Em relação aos estudos sobre a utilização de CI para o tratamento da sibilância em lactentes, existem diferenças nos critérios de seleção das crianças, nas estratégias de tratamento, na coleta dos dados e nos desfechos considerados 8,[13][14][15][16][17][18][19][20][21][22][23][24][25] . Apesar disso, é possível concluir que a utilização de CI em lactentes pode, em algumas situações, possibilitar um melhor controle dos sintomas que, porém, não se sustenta após a suspensão do mesmo, ou seja, não interfere A principal limitação do presente estudo compreende o fato de as frequências de uso de CO e CI serem estimadas pelo relato dos pais ou responsáveis pela criança e não através de registros médicos, o que seria mais confiável.…”
Section: Características N (%)unclassified
“…Por outro lado, estudos realizados em crianças nos primeiros 3 anos de vida com budesonida nebulizada ou montelucaste oral de maneira intermitente demonstraram que não houve melhora significativa nos desfechos primários, como dias livres de sintomas, persistência de sibilância e redução no uso de corticosteroide oral 61,62 . Entretanto, Bacharier et al observaram que naqueles com APIm positivo, o tratamento por 1 semana com budesonida nebulizada ou montelucaste oral proporcionou menor uso de corticosteroide oral, significativa redução de episódios graves de sibilos e melhora do escore respiratório, quando comparados com as crianças que tiveram APIm negativo 62 .…”
Section: Tratamento Da Sibilância/asma Em Pré-escolaresunclassified